Epistemic uncertainty: Turkish children with specific language impairment and their comprehension of tense and aspect - Yarbay Duman, Tuba; Topbaş, Seyhun (Wiley, 2016)
BackgroundImpairments in tense morphology are characteristic of English-speaking children with specific language impairment (SLI). Recent studies have investigated the role that aspect plays in the difficulties found in tense morphology. It has been suggested that children with SLI are less sensitive to aspect and its interaction with tense than typically developing (TD) children. Profound impairment in past tense morphology compared with the present in this population was explained by a breakdown in the association between event completion information and past tense. To date, research on tense morphology in this population has not examined all three tense conditions in a single study. AimsTo examine whether monolingual Turkish-speaking children with SLI exhibit deficits in comprehending tense and aspect morphology, and, if so, whether these deficits are restricted to completed events (past tense) or also occur for incomplete non-past events (future and present tense). Methods & ProceduresA sentence-picture matching task was administered to 36 monolingual Turkish-speaking children: 13 with SLI (mean age = 6;9 years) and 23 age-matched TD children (mean age = 6;5 years). Upon hearing a sentence, each child had to select between a target (past, present or future) and a distracter picture. Tense and aspect information could only be established from verb morphology. Outcomes & ResultsThe SLI group had lower accuracy than the TD group on all test conditions. For both groups, present tense had the highest accuracy scores. Performance scores within the SLI group showed the following hierarchy from easy to difficult: present > future > past. Conclusions & ImplicationsTurkish children with SLI have deficits in comprehending tense and aspect morphology. Although comprehending past was more difficult than non-past (present and future), future was more difficult to comprehend than the present. This disassociation between two non-past incomplete events indicates that the underlying difficulties comprehending (past) tense-aspect is not restricted to event completion in past tense contexts. This finding raises the possibility that in children with SLI, non-temporal epistemic functions of verb morphology (i.e., certainty, probability or possibility of an event occurring) might play a role in efficient understanding of tense and aspect morphology. If so, children with SLI may benefit from language therapy focused on the epistemic functions of verb morphology to improve comprehension of tense and aspect.
WOS: 000387125300009
PubMed ID: 27074978
Keywords: Tense; Aspect; Specific Language Impairment (SLI); Turkish; Morphosyntax-Semantics Interface; Epistemic Uncertainty